The Effect of Cellulase Addition to Rice Bran Tempeh Containing Diet on Performance, Body Dimension and Carcass Quality in Broilers Raised on the Coastal Area - Santoso, Urip; Brata, Bieng; Kususiyah, Kususiyah; Dani, Muhammad; Ihsan, Ilham Nur; Firdiansyah, Mica; Antomi, Robi (Universitas Halu Oleo, 2023)
This study evaluated the effect of cellulase enzymes addition to a rice bran tempeh-containing diet on performance, body dimension, and carcass quality. Two hundred broilers aged 15 days were divided into 4 treatment groups of 5 replications each, as follows: P1=20% rice bran tempeh plus 0% cellulase; P2 =20% rice bran tempeh plus 0.05% cellulase; P3=20% rice bran tempeh plus 0.1% cellulase, and P4=20% rice bran tempeh plus 0.15% cellulase. The results showed that the addition of cellulase had no significant effect on body weight, body weight gain, feed intake, feed conversion ratio, internal organ weight, carcass quality, and meat organoleptic properties (P>0.05) but significantly affected beak length, neck length, shank circumference, body length, tibia length (P